Between a Rock and a Hard Place: Border Minorities in China's Foreign Relations with South Asia. Issue 3 (27th May 2019) - Chand, Bibek; Danner, Lukas K.
ABSTRACT: This article takes a closer look at how China's government deals with border minorities in the foreign relations with its neighboring South Asian states. To secure its periphery, China has been known to push its neighbors to support border security, including repressive measures against refugee populations which could potentially threaten China's domestic peace by inciting or supporting secessionist movements. This study highlights the roles of the Tibetan and Uighur minorities in the relations of China with adjacent states in South Asia. For the Tibetan minority, the article will analyze Sino-Nepalese as well as Sino-Indian relations; concerning the Uighur minority, Sino-Pakistani relations will be highlighted. These case studies promise to be interesting also because of the range of relationships between China and these countries, Pakistan being a relatively close ally, Nepal a buffer state in which China and India compete for power, and India being at least a competitor state, if not arch-enemy—given still existing border disputes. India and Nepal house the first and second largest Tibetan refugee populations worldwide, respectively, while only a small Uighur population lives in Pakistan. Expected results should show the relative importance of border minorities and therefore, Chinese domestic politics in foreign relations with the selected cases.